DECLARATION OF PRAMBANAN TEMPLE AND BOROBUDUR TEMPLE AS PLACES OF WORSHIP FOR HINDUS AND BUDDHISTS: A Process of Tarka Vāda (Negotiation) Towards A Memorandum of Agreement - Budiana Setiawan (Perkumpulan Organisasi Profesi DPP Dosen Hindu Indonesia (DHI) Bekerja sama dengan Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar dan Institut Agama Hindu Negeri Tampung Penyang Palangka Raya, 2024)
In the beginning of 2021, the Minister of Religious Affairs conveyed the idea of creating Borobudur Temple and Prambanan Temple as places of worship for Buddhists and Hindus. The Minister of Religious Affairs's statement was followed up with the formation of the Working Team of the Temple Designation. The purpose of the formation of the working team was to prepare a memorandum of agreement between the Directorate General of Culture and the Director General of Hindu Community Guidance and the Director General of Buddhist Community Guidance. However, the signature of the memorandum of agreement was only realized one year later, after going through a long series of tarka vāda (negotiations). What is the tarka vāda strategy carried out by the Working Team of the Temple Designation? Which parties are involved and what is their role in the tarka vāda? The research reveals obstacles and opportunities when carrying out a series of tarka vāda to obtain the truth. The research is descriptive and qualitative with data collection methods through autoethnography and supported by kinds of literature review. The research results show that the main problem faced by the Working Team of the Temple Designation is synchronizing the interests of the Directorate General of Culture with the Directorate General for Guidance of Hindu Society and the Directorate General for Guidance of Buddhist Society. In this case, the Ministry of Religious Affairs' utilization interests is supported by agencies with an interest in benefiting of devise and economic from the number of tourists who come, namely: (a) Borobudur Temple, Prambanan, and Ratu Boko Tourist Parks Company, (b) Ministry of Tourism and Creative Economy, (c) The Government of Central Java Province, and (d) The Government of Yogyakarta Special Region. The moderator is the Assistant Deputy for Religious Moderation, The Ministry of Coordinator for Human Development and Culture. The involvement of the agencies are the reason why the signature of the Memorandum of Agreement is successful.